The Comparative Study between Twisted and Non-Twisted Distribution Line for Photovoltaic System Subjected to Induced Voltage Generated by Impulse Voltage - Nur Hidayu Abdul Rahim; Zikri Abadi Baharudin; Md Nazri Othman; Puteri Nur Suhaila Ab Rahman (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The recent advancement of renewable energy sources and specifically photovoltaic system has resulted in outdoor installations of large power stations. A photovoltaic system is exposed to extreme ambient conditions due to the lightning strike activity that generated induced overvoltage which have a high tendency to affect the electrical apparatus especially renewable energy plant that directly exposed to this source. This study is performed through experimental work by comparing the effect of induced overvoltage propagation upon between the twisted and non-twisted distribution line for photovoltaic system. The induced voltage is performed by using lightning impulse generator. It is found that the maximum voltage of the unwanted signal is proportional with the distant of the specimen. The closer distant between solar panel material and spark discharge, the more serious effect would occur due to the induced overvoltage.